2002
DOI: 10.3727/036012902816026068
|View full text |Cite
|
Sign up to set email alerts
|

Biophoton Emission from Fingernails and Fingerprints of Living Human Subjects

Abstract: Biophotons emitted from the center of fingernails and fingerprints from living humans are measured for twenty healthy subjects. We devised a dark box with a photo multiplier tube (H6180-01, Hamamatsu, Japan) whose spectral range is 300 nm to approximately 650 nm and a mount with a light-receiving hole of diameter 8 mm such that biophotons from the small circular area of nail or print of each finger are detected. Significantly more biophotons are emitted from fingernail than fingerprint for each finger of every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They also reported that after acupuncture treatment, the left and right difference in biophoton emission was dramatically reduced: in each case the lateral difference was normalised after the treatment. The Korean research group also utilised a photomultiplier with an aperture of 8 mm diameter, such that photons from point-like sources could be detected [26]. Biophotons emitted from the fingernails and fingerprints of 20 healthy subjects were measured.…”
Section: Biophoton Emission Of Hands From the Perspective Of Traditiomentioning
confidence: 99%
“…They also reported that after acupuncture treatment, the left and right difference in biophoton emission was dramatically reduced: in each case the lateral difference was normalised after the treatment. The Korean research group also utilised a photomultiplier with an aperture of 8 mm diameter, such that photons from point-like sources could be detected [26]. Biophotons emitted from the fingernails and fingerprints of 20 healthy subjects were measured.…”
Section: Biophoton Emission Of Hands From the Perspective Of Traditiomentioning
confidence: 99%
“…Of the 56 included studies, 28 were characterized as observational and descriptive studies, out of which 20 studies used whole body[56], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], 3 blood cells[85], [86], [87], 3 saliva[64], [88], [89], 1 blood plasma[90], and 1 breath[91] as systems of research. The details of these studies will be reported on in future publications.…”
Section: Resultsmentioning
confidence: 99%
“…All the knowledge of some predecessors [Mandel, 1986], [Moss, 1979], [Kim, 2002], [Korotkov, 1999], [Popp, 1998], [Popp et al, 1992], [Rubik, 2002a], [Rubik, 2002b] was used by the first author of this article to get the abilities to succeed in making the present measurements. All the measurements could be made due to the capacity of the article's first author to determine his body to respond very quickly to his own intentions and will.…”
Section: Discussionmentioning
confidence: 99%